LSCF-CGO nanocomposite cathodes deposited in a single step by spraypyrolysis. - Dos-Santos-Gómez, Lucía; Porras-Vázquez, José Manuel; Ramírez-Losilla, Enrique; Martín-Jiménez, Francisco de Paula; Ramos-Barrado, José Ramón; Marrero-López, David (Elsevier, 2018)
La0.6Sr0.4Co0.2Fe0.8O3-δ-Ce0.9Gd0.1O1.95 (LSCF-CGO) nanostructured cathodes with different LSCF-content are prepared in a single step by spray-pyrolysis deposition, simplifying notably the fabrication process compared to the traditional methods. The phase formation, structure, microstructure and electrochemical properties of the cathodes are investigated as a function of the CGO-content and the temperature by using X-ray diffraction, electron microscopy and impedance spectroscopy. The addition of CGO to LSCF limits the grain growth, giving rise to fine particles of approximately 30 nm of diameter after sintering at 800 °C. A small particle size of 50 nm is retained even after sintering at 1000 °C. However, the polarization resistance, determined by impedance spectroscopy, is not significantly improved with the CGO-addition. The performance of these nanocomposite electrodes, investigated in NiOeCGO anode-supported cells, shows an improved power density of 0.9 Wcm−2 at 650 °C, compared to 0.56 Wcm−2 for a conventional screen-printed cathode.
Keywords: Pilas de combustible; Electroquímica; Solid oxide fuel cells; Spray-pyrolysis; Composite cathode